A PBNM and economic incentive-based defensive mechanism against DDoS attacks. Issue 3 (4th March 2022) - Dahiya, Amrita; Gupta, B. B.
ABSTRACT: In this paper, a policy-based network management (PBNM) strategy has been proposed to defend DDoS attack along with maintaining Quality of Service (QoS) for legitimate users. During cautious or alert level users having a contract are only allowed to enter into the network. Moreover, PBNM has been used for enabling users to negotiate with the service provider dynamically on cost and types of services. Extensive experimentations have been carried out to check the validity of the proposed model. Experimentation has been performed in two phases. In first phase reachability condition will be checked on PN2 simulator and SPIN while in second phase, NS-2 is used to monitor the performance of the proposed model according to networking parameters. Results from implementation show the supremacy of the proposed model.